Losing her marbles - McLean, Lloyd; Konye, Paul (Macmillan South Yarra, Vic., 1998)
the story of a woman confronting the gradual loss of her mental faculties. The novel blends sharp wit and emotional insight, offering a deep exploration of the protagonist$1 (Bs inner world as she grapples with memory loss and identity, while those around her struggle to understand her transformation.s